A relação interdisciplinar entre física e filosofia no terceiro ano do ensino médio em uma escola pública na cidade de Manaus - Carmo, Wanilce do Socorro Pimentel do (2016)
This dissertation brings proposes the interdisciplinary relationship between physics and philosophy in a public high school in the city of Manaus. In our research we have the participation of three teachers and two Degree in Physics and a professor degree in Philosophy and also two classes of third year, anchored as a theoretical renowned authors as Japiassu (1976) Finance (2012) Luck (2010 ), among others. The methodology approach is mixed research with qualitative approach using as technique of data collection of: half structured interview, observation and questionnaire analyzed by Likert scale. For data analysis was used the content analysis technique. The results signaled that interdisciplinary happens superficially, since the teachers bring to their speech in class, mediating content of dealing with both the philosophy which is the basis of all sciences and physics, understanding that Philosophy is the basis of all sciences, however it is clear that the teaching plan interdisciplinary is not included, although the NCP is present. Aiming to consolidate student and teacher, teaching, learning at the heart of reflection, the criticality involving them in the applicability of pedagogical practice